HUMAN VALUES IN NUSANTARA AND WESTERN LITERATURE: CHARACTER BUILDING STRATEGIES THROUGH LOCAL WISDOM BASED ON TRADITIONAL ECOLOGICAL KNOWLEDGE - Christiana Evy Tri Widyahening; Siti Supeni (GeoEco, 2026)
The increasingly intense currents of globalisation and modernisation have led to moral degradation, ecological crises, and a weakening of human values and environmental awareness in society. Literature, as a product of culture and a reflection of human thought, has a strategic role in transmitting ethical, social, and ecological values that contribute to character building. However, contemporary literary studies and educational practices still tend to ignore local wisdom, especially values derived from Traditional Ecological Knowledge (TEK). Nusantara literature represents the values of collective ethics, harmony between humans and nature, and spirituality rooted in traditional ecological knowledge, while Western literature emphasises individuality, rationality, and moral autonomy. These differences in value orientation show the potential for complementarity in responding to today's moral and ecological issues. Through a qualitative comparative analysis of Nusantara and Western literary works, this article shows that the integration of TEK-based local wisdom in literary learning can strengthen character education, foster ecological ethics, and support cultural and environmental sustainability. The TEK-based literary approach is a contextual and transformative strategy in responding to the challenge of the degradation of human values in the global era.